Keabsahan Pemenuhan Suatu Perjanjian yang Tidak Memiliki Alas Hukum Yang Sah - Setiawan, Alberich Martin; Suryawati, Nany (Universitas Batanghari Jambi, 2024)
The agreement is the main key in helping the interests of each party to meet their needs or interests. This research focuses on the legal consequences of agreements that do not have a power of attorney that cause losses to parties who bind themselves to the agreement. This research uses normative juridical methods with data collected through laws and several articles and journals. Perform a mandatory agreement to meet the applicable conditions in accordance with regulations. Violation of objective terms in article 1320 of the Civil Code may lead to defects in the agreement. This occurs due to the absence of a power of attorney and the signing is not carried out by a company representative who has the authority in accordance with the Limited Liability Company Law. Both of these things make the agreement made invalid and null and void. Further legal consequences can lead to unlawful acts. This occurs because the agreement that should be null and void still continues, causing losses to one of the parties. Losses that are formally and materially experienced by PT. J thus making PT. S is obliged to provide compensation. Compensation cannot be separated from illegal acts due to ongoing agreements that should be canceled by law.